Tetraarylantimony 2,2′-bipyridinecarboxylates: synthesis, photophysical and molecular docking studies - Ekaterina V. Artem’eva; Vladimir V. Sharutin; Alexey P. Krinochkin; Yulia M. Sayfutdinova; Il’ya I. Butorin; Vasiliy S. Gaviko; Yaroslav K. Shtaitz; Maria I. Valieva; Igor S. Kovalev; Olga V. Shabunina; Igor L. Nikonov; Dmitry S. Kopchuk; et al. (Chimica Techno Acta)
Tetraarylantimony(V) carboxylates based on 5-carboxyl and 6-carboxyl 2,2’-bipyridines (4 compounds) were synthesized for the first time. The structure of one of the compounds was confirmed by X-ray diffraction analysis. It was shown that the carboxyl group participates in the coordination of the antimony(V) cation, but the bipyridine fragment does not. The antitumor activity of the new complexes was assessed by molecular docking, and the most probable targets were determined. It was shown that the affinity of ligands to them is higher than that of the corresponding complexes. The best results were obtained for complex 3a; its inhibition of VEGFR2 is 74% more effective compared to the native ligand. In addition, the primary photophysical properties of the new carboxylates in acetonitrile solutions were studied. It was shown that the luminescence quantum yield values strongly depend on the position of the carboxyl group: for 5-substituted compounds they reach 65.0%, while for 6-substituted ones they have an extremely low ( 0.1%) value. At the same time, the absorption and emission maxima are within 300–314 nm and 364–403 nm, respectively.